Fetal movements as a predictor of health. (September 2016) - Lai, Jonathan; Nowlan, Niamh C.; Vaidyanathan, Ravi; Shaw, Caroline J.; Lees, Christoph C.
Abstract: The key determinant to a fetus maintaining its health is through adequate perfusion and oxygen transfer mediated by the functioning placenta. When this equilibrium is distorted, a number of physiological changes, including reduced fetal growth, occur to favor survival. Technologies have been developed to monitor these changes with a view to prolong intrauterine maturity while reducing the risks of stillbirth. Many of these strategies involve complex interpretation, for example Doppler ultrasound for fetal blood flow and computerized analysis of fetal heart rate changes. However, even with these modalities of fetal assessment to determine the optimal timing of delivery, fetal movements remain integral to clinical decision‐making. In high‐risk cohorts with fetal growth restriction, the manifestation of a reduction in perceived movements may warrant an expedited delivery. Despite this, there has been little evolution in the development of technologies to objectively evaluate fetal movement behavior for clinical application. This review explores the available literature on the value of fetal movement analysis as a method of assessing fetal wellbeing, and demonstrates how interdisciplinary developments in this area may aid in the improvement of clinical outcomes.